1989
DOI: 10.1111/j.1467-6494.1989.tb00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Shakespeare's Sonnets: A Case of and for Single–Case Historiometry

Abstract: The two oldest forms of psychohistory, as genencally defined, are psychc*iography (ldiographic, qualitative, and single-case) and histonometry (nomothetic, quantitative, and multiple-case) In practice this distinction gets blurred, both because psychobiography is often nomothetic (e g , psychoanalytic) and because histonometry may work with A' = 1 After outlining the assets of single-case histonometry, a specific case is given in an analysis of the 154 sonnets of William Shakespeare These sonnets were first re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 51 publications
0
50
1
3
Order By: Relevance
“…Trying to find quantitative structural predictors for the aesthetic success – a variable that is assumed to be highly correlated with liking – of the 154 Shakespeare sonnets, Simonton (1989, 1990) isolated four factors accounting for the superiority of very popular sonnets…”
Section: Multiword Expressionsmentioning
confidence: 99%
“…Trying to find quantitative structural predictors for the aesthetic success – a variable that is assumed to be highly correlated with liking – of the 154 Shakespeare sonnets, Simonton (1989, 1990) isolated four factors accounting for the superiority of very popular sonnets…”
Section: Multiword Expressionsmentioning
confidence: 99%
“…Previous research on this topic has utilized such diverse populations as scientists in various disciplines (Simonton, 2003), writers and poets (Ludwig, 1994;Simonton, 1989), and composers of classical music (Simonton, 1977;Kozbelt, 2004Kozbelt, , 2005). Simonton's study of the pattern of lifetime productivity of 10 classical composers reported a correlation between major and minor works within periods over a composer's career and, most critically, that the proportion of major works produced per unit time remained constant over those composers' careers (Simonton, 1977).…”
mentioning
confidence: 99%
“…One example is single-case historiometry, which examines the life or career of just one historic figure using quantitative methods (e.g., Rosenberg, 1989;Rosenberg & Jones, 1972). Yet this technical feat is invariably accomplished by slicing the individual's life into smaller units, sach as consecutive periods of adulthood (e.g., Simonton, 1977a;Weisberg, 1994) or separate acts of achievement (e.g., Simonton, 1989a). Nevertheless, because, this methodological legerdemain merely obtains multiple cases from a single case by shrinking the unii of analysis, this approach can still be classed as a special variety of historiometry.…”
Section: Four Research Traditionsmentioning
confidence: 99%